2010
DOI: 10.1371/journal.pone.0011483
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Target Genes Are Silenced in Multiple Myeloma

Abstract: Multiple myeloma (MM) is a genetically heterogeneous disease, which to date remains fatal. Finding a common mechanism for initiation and progression of MM continues to be challenging. By means of integrative genomics, we identified an underexpressed gene signature in MM patient cells compared to normal counterpart plasma cells. This profile was enriched for previously defined H3K27-tri-methylated genes, targets of the Polycomb group (PcG) proteins in human embryonic fibroblasts. Additionally, the silenced gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 50 publications
8
118
1
Order By: Relevance
“…H3K27me3 is usually associated with transcriptional repression. 19 However, in the present study, the increase of H3K27me3 on MSTN promoter correlated with higher MSTN mRNA expression. Recently, advances in the study of chromatin modifications revealed the functional significance of cross-talk among modifications.…”
Section: Methodscontrasting
confidence: 69%
See 1 more Smart Citation
“…H3K27me3 is usually associated with transcriptional repression. 19 However, in the present study, the increase of H3K27me3 on MSTN promoter correlated with higher MSTN mRNA expression. Recently, advances in the study of chromatin modifications revealed the functional significance of cross-talk among modifications.…”
Section: Methodscontrasting
confidence: 69%
“…18,19 However, the same histone modification may exert different effects on gene transcription under different circumstances, depending on genomic location, tissue/cell types or developmental stages. For instance, H3K9me3 is a key repressive marker associated with gene silencing, but it can also be associated with transcriptional activation.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In multiple myeloma, it has been shown that PRC2 target genes are most often found silenced in myeloma (15). Exploration of EZH2 inhibitors in multiple myeloma models is therefore an attractive field of research which may lead to a broader understanding of multiple myeloma biology and will guide the development of new targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] EZH2 is expressed in undifferentiated stem-like cancer cells and promotes cancer cell proliferation and metastasis formation by repressing several tumor suppressor genes. 15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype.…”
Section: Introductionmentioning
confidence: 99%